"This job is horrible!" Reflections on Transitions to Virtual Learning. (3rd April 2022) - Arce-Trigatti, Andrea; Silber-Furman, Dorota
Abstract: Practitioner inquiry into the challenges of transitioning to online learning revealed key strategies for both teachers and students on the time, commitment, effort, and dedication needed to successfully engage with virtual learning.